Incidencia de queratoconjuntivitis seca en caninos "canis lupus familiaris" braquiocefálicos, en la ciudad de machala. - Sanchez Ordoñez, Nelly Mayra (Machala : Universidad Técnica de Machala, 2022)
The eye is the main organ of the visual system, it captures the images and transforms them into an electrical signal to the optic nerve, to transfer to the brain and process the image. In dogs there is a certain predisposition to suffer some eye damage, specifically the brachiocephalic due to their anatomical structure. They have a short and wide skull and face due to the shortening of the bones, the tissues change due to the space limit, presenting reduced nostrils, more exposed eyes that generate greater tear evaporation, resulting in keratoconjunctivitis sicca. Inflammatory disease altering the cornea and conjunctiva due to qualitative alterations, generating problems such as dryness of the cornea, ulcerations, pigmentation, vascularization and quantitative, which is the decrease in the significant amount of tear production. They are formed from a mixture of secretions excreted by the lacrimal gland, tarsal glands and apocrine ciliary glands secrete triglycerides, lipids, phospholipids, free sterols as well as mucin and an aqueous part to form the precorneal film. Its function is to lubricate the eyelids, prevents the cornea from drying out, provides oxygen, has antimicrobial substances to cover the cornea from infections, removes foreign bodies from the cornea, prevents dehydration. The objective of the work was to determine the incidence of dry keratoconjunctivitis, intraocular pressure and blood glucose, with quantitative diagnostic methods Schirmer test, tonometer and glucometer. The methodology used was data collection and clinical evaluation of the ocular adnexa such as the eyeball, conjunctiva, eyelids, third eyelid. Apparently healthy brachiocephalic canines from the city of Machala were evaluated taking into account sex and age. It was divided into 3 study groups from 6 months to 2 years, from 2.5 to 5 years and older than 6 years. Keratoconjunctivitis sicca was diagnosed by means of the Schirmer test, intraocular pressure by tonometry (Schiotz indented tonometer) and blood glucose by means of a glucometer, taking a blood sample from the phalanx, ruling out patients with any glycemic alteration. After statistical analysis of a total of 33 brachycephalic dogs sampled, 27.3% were positive for keratoconjunctivitis sicca. According to age, canines from 6 months to 2 years old presented 16.6% incidence, from 2.5 to 5 years old 40% and older than 6 years old 27.3%. In representation of the sex of a total of 18 males, 22.2% have the disease and of 15 females, 33.3% are positive. Regarding (PIO) 33.3% have high intraocular pressure, 27.3% low and 39.4% normal, in representation of age, the group with the highest rate of elevated intraocular pressure is 6 years in forward with a percentage of 54.5% and finally blood glucose 12.1% of the total presented hyperglycemia, the rest normal with a higher incidence in canines from 2.5 to 5 years of 10 patients, 20% presented hyperglycemia. In conclusion, the Chi-square statistical test performed to determine if there is a dependency relationship between the Schirmer test and glucose categories, a significance value of 0.237 is obtained; which is greater than 0.05 (p value), therefore the null hypothesis is accepted and it is concluded that the variables Schirmer's test and intraocular pressure are not related.
El ojo es el órgano principal del sistema visual, capta las imágenes y las transforma en señal eléctrica al nervio óptico, para trasladar al cerebro y procesar la imagen. En los perros existe cierta predisposición a sufrir algún daño ocular específicamente los braquiocefálicos debido a su estructura anatómica. Presentan el cráneo y rostro corto y ancho por el acortamiento de los huesos los tejidos cambian por el límite de espacio presentando orificios nasales reducidos, ojos más expuestos que genera una mayor evaporación lagrimal dando como resultado queratoconjuntivitis seca. Enfermedad inflamatoria alterando córnea y conjuntiva por alteraciones de forma cualitativa generando problemas como resequedad de la córnea, ulceraciones, pigmentación, vascularización y cuantitativa que es la disminución de la cantidad significativa de la producción lagrimal. Se forman de una mezcla de secreciones excretadas por la glándula lagrimal, glándulas tarsales y glándulas ciliares apocrinas segregan triglicéridos, lípidos, fosfolípidos, esteroles libres así como mucina y una parte acuosa para formar la película precorneal. Su función es lubricar los párpados, impide la desecación de la córnea, aporta oxígeno, tiene sustancias antimicrobianas para cubrir la córnea de infecciones, elimina cuerpos extraños de la córnea, evita la deshidratación. El objetivo del trabajo fue determinar la incidencia de queratoconjuntivitis seca, presión intraocular y glucosa en sangre, con métodos diagnósticos cuantitativos test de schirmer, tonómetro y glucómetro. La metodología empleada fue la toma de datos y evaluación clínica de los anexos oculares como globo ocular, conjuntiva, párpados, tercer párpado. Se evaluó caninos braquiocefálicos de la ciudad de Machala aparentemente sanos tomando en cuenta sexo y medida etaria. Se dividió en 3 grupos de estudio de 6 meses a 2 años, de 2,5 a 5 años y mayores a 6 años. Se diagnosticó queratoconjuntivitis seca mediante test de schirmer, la presión intraocular por tonometría ( tonómetro indentado de schiotz) y glucosa en sangre mediante glucómetro tomando muestra de sangre de falange descartando pacientes con con alguna alteración de glucemia . Luego del análisis estadístico de un total de 33 perros braquiocefálicos muestreados, el 27,3% fueron positivos a queratoconjuntivitis seca. Según edad los caninos de 6 meses a 2 años presentaron el 16,6% de incidencia, de 2,5 a 5 años 40% y mayores a 6 años 27,3%. En representación al sexo de un total de 18 machos el 22,2% presentan la enfermedad y de 15 hembras el 33,3% son positivas. Con respecto a (PÍO) el 33,3% tiene presión intraocular alta, el 27,3% baja y el 39,4% normal, en representación a la edad el grupo con mayor índice de Presión intraocular elevada es el de 6 años en adelante con un porcentaje de 54,5% y finalmente glucosa en sangre el 12,1% del total presentaron hiperglucemia el resto normal con mayor incidencia en caninos de 2,5 a 5 años de 10 paciente el 20% presentó hiperglicemia. En conclusión la prueba estadística Chi-cuadrado realizada para determinar si existe relación de dependencia entre las categorías test de schirmer y glucosa se obtiene un valor de significación de 0,237; el cual es mayor a 0.05 (valor p), por lo tanto se acepta la hipótesis nula y se concluye que las variables test de schirmer y presión intraocular no se encuentran relacionadas.
Keywords: OJO; QUERATOCONJUNTIVITIS; SCHIRMER; BRAQUIOCEFÁLICO